Fulminant myocarditis managed with pulsatile extracorporeal life support; use of Twin Pulse Life support (T-PLS(®)) - Cho, Eun Jeung (BioMed Central, 2011)
Fulminant myocarditis frequently results in severe hemodynamic deterioration. High-dose vasopressors or sometimes mechanical circulatory support are required. We report on two cases of fulminant myocarditis successfully treated with pulsatile extracorporeal life support (T-PLS(®), Twin Pulse Life support, New heart bio.BHK, Seoul, Korea). With T-PLS, we were able to provide mechanical support to patients until they recovered completely.